Topological states in boron phosphide with zinc-blende structure - Li, Yang (Frontiers in Materials, 2022)
The field of topological states in phonon of solids have been rapidly developing in recent years. This work examined the phonon dispersion of a compound Boron Phosphide (BP) with a Zinc-Blende structure via first-principle calculation. The results show that BP is a stable compound in theory and hosts rich topological signatures in its phonon dispersion. Specifically, Weyl and quadratic nodal line states can be found in the acoustic branches, and triple point and quadratic contact triple point can be found in the optical branches. It is hoped that the rich topological states in BP can be imaged by inelastic x-ray scattering or neutron scattering in the near future.